Growth of Corn Germination (Zea mays L) on Remediated Nickel Mining Waste Media with Fertilizer - akbar, Irham; Rahim, Iradhatullah; Putera, Muh Ikbal; Sukmawati, Sukmawati; Qadri, Sri Nur (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
This study aims to evaluate the effectiveness of bioremediation using bio-fertilizers on the early growth of corn (Zea mays L.) in soil from former nickel mining sites. The study was conducted by observing soil characteristics and plant growth parameters, including soil texture, moisture content, cation exchange capacity (CEC), and macro nutrient content (N, P?O?, and K?O). Treatment L4P1 (location Sorowako with PGPR application) showed the best physical and chemical results, with the highest CEC value (40.65 cmol(+)/kg) and balanced macro nutrient content. Corn plant growth also showed a positive response to this treatment, indicated by the number of leaves (4.67), plant height (39.70 cm), leaf length (29.51 cm), as well as higher dry and wet weights compared to other treatments. Treatment P1 generally provided the most consistent and superior results compared to P2 and P3, demonstrating the effectiveness of the microbial formula in improving soil quality. degraded. In contrast, the L5 treatment showed the lowest results on almost all parameters. These results indicate that bioremediation with biofertilizers, particularly using PGPR (P1), has great potential in reclaiming former nickel mining soils and supporting food crop productivity on marginal lands